Definite Condition of the Evolutionary $\vec{p}(x)$−Laplacian Equation (Analysis in Theory and Applications, 2022)
For the nonlinear degenerate parabolic equations, how to find an appropriate boundary value condition to ensure the well-posedness of weak solution has beenan interesting and challenging problem. In this paper, we develop the general characteristic function method to study the stability of weak solutions based on a partialboundary value condition.